Occupation and parkinsonism in three movement disorders clinics. - Goldman SM; Tanner CM; Olanow CW; Watts RL; Field RD; Langston JW (Neurology)
BACKGROUND: Few occupational risk factors for Parkinson disease (PD) have been identified. Healthcare, teaching, and farming have been associated with increased risk, while welding has been proposed to accelerate age at PD onset. The aim of the present study was to investigate occupational associations with PD or parkinsonism drawing from three different movement disorders clinics. METHODS: Medical records of 2,249 consecutive patients with PD or parkinsonism from specialty clinics in Sunnyvale, CA, New York, NY, and Atlanta, GA, were reviewed for primary lifetime occupation. Job frequencies were compared with Department of Labor regional statistics. PD diagnosis age and risk of diagnosis < or =50 were determined for each job. RESULTS: Physicians/dentists, farmers, and teachers were significantly more common than expected among PD patients, as were lawyers, scientists, and religion-related jobs. Computer programmers had a younger age at PD diagnosis, and risk of diagnosis < or =50 was greater in computer programmers and technicians. CONCLUSIONS: Consistent with prior studies, healthcare, teaching, and farming were common occupations in Parkinson disease (PD) patients, but welders were not over-represented. Even though several occupations were associated with younger age at PD diagnosis, these results may reflect biases inherent in specialty clinic surveys, including over-representation of younger, employed, and insured patients. Carefully designed analytic studies utilizing appropriate control populations will be required to test hypotheses regarding occupation and PD risk.